Bürgerämter in Deutschland Organisationswandel und digitale Transformation - Jörg Bogumil (Modernisierung des öffentlichen Sektors (, 2019)
Abstract For many years, German municipal offices were regarded as the model of success in terms of modernising local administrative services in order to cater more to ordinary citizens. However, as a result of long waiting times and complaints from staff about deteriorating working conditions, municipal offices have come under increasing pressure in recent years. This study conducts a comprehensive analysis of the current organisational, personnel and technical situation in German municipal offices. Its findings reveal that there has been a change in their organisation, especially through the introduction of consultations by appointment and the increasing use of digital administrative processes. Despite an undeniable increase in the staff's workload at such local authority offices, mayors, personnel representatives and citizens are highly satisfied with the services they provide. Nonetheless, further investment in their staff is still necessary and the reform measures already implemented need to be expanded to make the online services they offer more user-friendly. Zusammenfassung Bürgerämter galten lange Zeit als das Erfolgsmodell der Verwaltungsmodernisierung in Richtung einer verstärkten Bürgerorientierung, sind in den letzten Jahren aber durch lange Wartezeiten und Klagen von Seiten der Mitarbeiterschaft über sich verschlechternde Arbeitsbedingungen unter Druck geraten. In der Studie wird eine umfassende Analyse der aktuellen organisatorischen, personellen und technischen Situation in den deutschen Bürgerämtern vorgenommen. Im Ergebnis zeigen sich ein Organisationswandel insbesondere durch die Einführung von Terminsprechstunden und die zunehmende Nutzung digitaler Verwaltungsprozesse. Trotz einer unbestrittenen Zunahme der Arbeitsbelastung der Mitarbeiter besteht übereinstimmend eine hohe Zufriedenheit mit den Leistungen der Bürgerämter durch die Bürgermeister, Personalräte und Bürger. Notwendig sind weitere personelle Investitionen und ein Ausbau der Reformanstrengungen in Richtung einer größeren Nutzerfreundlichkeit von Online-Angeboten.